Enkulturasi Al-Qur’an Dan Radikalisme Agama - Farri Chatul Liqok (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2019)
The configuration of Islam in Indonesia can be said to have varied variations. This diversity is characterized by the emergence of radical Islam with exclusive, scriptural, puritanical, militant and extremist characteristics. The assumption is that acts of violence in the name of religion are the result of a lack of comprehension in understanding religious texts. Whereas al-Qur'an experiences enculturation that can be used as a projector to sort out the teachings of the Qur'an which are substantial-fundamental and symbolic-instrumental. Enculturation explains the interaction between culture and religion. The interaction occurred between revelation (al-Qur'an) with the traditions of the Arab community. What is seen is what is added to the revelations in the tradition, so that it can be sorted out which values ​​are substantial-fundamental and which are symbolic-instrumental which in the end is an incorrect understanding of the Qur'an especially those practiced with violence can be minimized. Konfigurasi Islam di Indonesia bisa dikatakan mempunyai ragam yang variatif. Keragaman tersebut diantaranya diwarnai dengan munculnya islam radikal yang berkarakter eksklusif, skriptual, puritan, militan, dan ekstrimis. Asumsinya bahwa adanya tindakan kekerasan yang mengatasnamakan agama merupakan akibat dari kurang komprehensifnya dalam memahami teks-teks agama. Padahal al-Qur’an mengalami enkulturasi yang bisa dijadikan proyektor untuk memilah antara ajaran Al-Qur’an yang substansial-fundamental dan simbolik-instrumental. Enkulturasi menjelaskan interaksi antara budaya dan agama. Interaksi tersebut terjadi antara wahyu (al-Qur’an) dengan tradisi masyarakat arab. Hal yang dilihat adalah apa yang ditambahkan wahyu dalam tradisi, sehingga dapat dipilah mana nilai yang substansial-fundamental dan mana yang simbolik-instrumental yang pada akhirnya pemahaman yang kurang tepat terhadap al-Qur’an terlebih yang dipraktekkan dengan kekerasan bisa diminimalisir.